Sport, Identity and Inclusion in Europe The Experiences of LGBTQ People in Sport - Hartmann-Tews, Ilse (Routledge Research in Sport, Culture and Society, 2023)
This book explores and critically assesses the challenges and experiences of LGBTQ people within sport in Europe. It presents cutting-edge research data and insights from across the continent, with a focus on sport policy, sport systems, and issues around anti-discrimination and inclusion. The book introduces the theoretical and methodological foundations of research into LGBTQ people in sport and then presents in-depth comparative surveys of systems and experiences in Austria, Belgium, France, Germany, Hungary, Italy, the UK, and Spain. A final section considers the effectiveness of policy in this area and motives for participation, and looks ahead at future directions in research, policy, and practice. Tracing the frontiers of our understanding of the experiences of LGBTQ people in contemporary Europe, this is fascinating reading for anybody with an interest in the sociology of sport, sport policy, LGBTQI studies, gender and sexuality studies, or cultural studies.